Multi-Product Dynamic Advertisement Planning in a Segmented Market - JHA, P. C.; AGGARWAL, Sugandha; GUPTA, Anshu; KAUL, Arshia; KRISHNAMOORTHY, Mohan (Yugoslav Journal of Operations Research; Vol 27 No 2 (2017), 2017)
In this paper, a dynamic multi-objective linear integer programming model is proposed to optimally distribute a firm’s advertising budget among multiple products and media in a segmented market. To make the media plan responsive to the changes in the market, the distribution is carried dynamically by dividing the planning horizon into smaller periods. The model incorporates the retention effect of reach due to the previous period advertising on current period and also considers a cross-product effect of advertising among the products. An application of the model is presented for an insurance firm that markets five different products, using goal programming approach. Keywords: Media Planning, Segmented Market, Multiple Products, Cross-Product Effect, Retention Factor, Dynamic Model.